2021
DOI: 10.1016/j.diagmicrobio.2021.115338
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection and COVID-19 severity in individuals with prior seasonal coronavirus infection

Abstract: We show that individuals with documented history of seasonal coronavirus have a similar SARS-CoV-2 infection rate and COVID-19 severity as those with no prior history of seasonal coronavirus. Our findings suggest prior infection with seasonal coronavirus does not provide immunity to subsequent infection with SARS-CoV-2.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…Ng et al 2020 found that less than 1% of pre-pandemic samples showed SARS-CoV-2 RBD binding antibodies. This suggests that the majority of HCoV antibodies do not cross-react with SARS-CoV-2 and is in keeping with our results that HCoV neutralisation is not correlated with SARS-CoV-2 neutralisation, nor does it provide protection against COVID-19, which is consistent with a similar study (30). On the other hand, a study observed that a recent HCoV infection may provide some degree of protection (31).…”
Section: Discussionsupporting
confidence: 93%
“…Ng et al 2020 found that less than 1% of pre-pandemic samples showed SARS-CoV-2 RBD binding antibodies. This suggests that the majority of HCoV antibodies do not cross-react with SARS-CoV-2 and is in keeping with our results that HCoV neutralisation is not correlated with SARS-CoV-2 neutralisation, nor does it provide protection against COVID-19, which is consistent with a similar study (30). On the other hand, a study observed that a recent HCoV infection may provide some degree of protection (31).…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, while both vaccination cohorts showed an absence of or reduction in boosting of cross-reactive responses, whether this absence is beneficial or detrimental cannot be determined from the data presented here. While some studies of natural infection have suggested that these boosted responses are not associated with protection, but instead with more severe disease ( Guo et al, 2021 ; Aydillo et al, 2021 ; Dugan et al, 2021 ; Lin et al, 2022 ; Anderson et al, 2021 ; Gombar et al, 2021 ), others have supported the opposite conclusion ( Aran et al, 2020 ; Dugas et al, 2021a ; Dugas et al, 2021b ). Collectively, these natural infection studies are challenged by the inability to distinguish between correlation and causation, and to separate contributions from humoral from cellular memory.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are conflicting reports on whether such crossreactivity gets translated into a protective immunity, thus leading to less severe disease. Indeed, it has been shown that crossreactive anti-HCoVs antibodies do not confer protection against SARS-CoV-2 infection nor to hospitalizations, though they are boosted upon SARS-CoV-2 infection (206,207). On the contrary, another study showed that recent HCoVs infections are associated with less severe COVID-19 (208).…”
Section: Previous Infection With Seasonal Coronavirusesmentioning
confidence: 99%